Modern quality management in hotel tourism - Vorina Anton; Veljković Božidar (Marketing (Beograd. 1991), 2012)
Tourism is a rapidly growing industry that requires explosive reaction of management. In order to achieve or even exceed guests' expectations, we must determine what their expectations for quality of service are. The employees are the heart of business. How do we integrate all the power of quality that we will become in the eyes of customers? This is the task of modern management in tourism. In this paper we present an analysis of quality in a casual sample of 333 guests in 42 different hotels in Slovenia and Croatia. Based on multiple linear regression analysis, we found that guests in the four-star hotels are more satisfied with the quality of offers as guests in three-star hotels. Statistically significant differences between the three-stars hotels and four-star hotel is reflected in the satisfaction with the quality of food and drink and its quick service, the price of the service, friendliness of staff to guests, and the arrangement of the restaurant, reception and rooms.